The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1155/2013/818157
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Attachment Disorder in the General Population: A Hidden ESSENCE Disorder

Abstract: Reactive attachment disorder (RAD) is a severe disorder of social functioning. Previous research has shown that children with RAD may have poor cognitive and language abilities; however, findings mainly come from biased, institutionalised samples. This paper describes the characteristics of all children who were given a suspected or likely diagnosis of reactive attachment disorder in an epidemiological study of approximately 1,600 children investigating the prevalence of RAD in the general population. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 21 publications
(26 reference statements)
3
28
0
Order By: Relevance
“…Results of the current study did show that children with persisting DSEB, as well as children with de novo DSEB, had a higher prevalence of ADHD than children without DSEB. This is consistent with evidence for comorbidity of DSED and ADHD (Gleason et al., ; Pritchett et al., ). However, there is also a possibility that parent‐reported DSEB was miss‐classified in some of the children with ADHD, because ADHD/ODD was not associated with the observational measures for DSEB.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Results of the current study did show that children with persisting DSEB, as well as children with de novo DSEB, had a higher prevalence of ADHD than children without DSEB. This is consistent with evidence for comorbidity of DSED and ADHD (Gleason et al., ; Pritchett et al., ). However, there is also a possibility that parent‐reported DSEB was miss‐classified in some of the children with ADHD, because ADHD/ODD was not associated with the observational measures for DSEB.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding clinical implications, DSEB could be overshadowed by comorbid ADHD symptoms and lead to selective treatment of ADHD symptoms in children without focus on parent‐child relation and social interaction, as has been discussed by Pritchett et al. (). On the other hand, a lack of understanding of etiology of DSEB in clinically referred children asks for cautious interpretation of DSEB in home‐reared children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consultation with experts on the advisory panel recommend that this model parameter be provisionally explored using recent research. 237 This research finds that the prevalence of RAD in the general population to be 1.4%. (This paper was published in 2013 after the cut-off point for our systematic review.…”
Section: Prevalence Of Severe Attachment Problemmentioning
confidence: 87%
“…Inhibited RAD is thought to be very rare beyond the specific context of maltreatment [14] but we have recently shown that the disinhibited form is far from being rare and has a prevalence of around 1.4% in a deprived population [15]—similar to or even higher than the population prevalence of ASD [16]. We have also found that children with RAD often have complex neurodevelopmental problems [17] and that, even after living for several years in loving adoptive families, these children can still have problems that are a major burden for themselves, their families, and their peers [18]. …”
Section: What Are the Maltreatment-associated Psychiatric Problems?mentioning
confidence: 99%